FAKTOR-FAKTOR YANG MEMENGARUHI MINAT MAHASISWA AKUNTANSI UNTUK BERKARIR SEBAGAI AKUNTAN PUBLIK (STUDI KASUS PADA MAHASISWA S1 JURUSAN AKUNTANSI UNIVERSITAS BRAWIJAYA) - Vista Rossita ; Wiwik Hidajah Ekowati , M.Si.,Ak.,CA
This study aims to determine the factors that influence the interest of_x000D_ accounting students in choosing a career as a public accountant. This study uses_x000D_ quantitative methods. The sample used amounted to 100 Accounting students_x000D_ from the faculties of economics and business, Universitas Brawijaya. The data_x000D_ collection method used is by distributing questionnaires. The statistical test tool_x000D_ used to process data is Partial Least Square (PLS) analysis. The results showed_x000D_ that: financial rewards, professional training, work environment, labor market_x000D_ considerations, and personality had a positive effect on the interest of accounting_x000D_ students in choosing careers as public accountants, while professional recognition_x000D_ factors, social values and work environment did not affect student interest_x000D_ accounting in choosing a career as a public accountant._x000D_ _x000D_ _x000D_ Keywords: interest, social values, family environment, public accountant